Third-Degree Price Discrimination in Two-Sided Markets - de Cornière, Alexandre; Mantovani, Andrea; Shekhar, Shiva (Management Science, 2025)
We investigate the welfare effects of third-degree price discrimination by a two-sided platform that enables interaction between buyers and sellers. Sellers are heterogeneous with respect to their per-interaction benefit, and, under price discrimination, the platform can condition its fee on sellers’ type. In a model with linear demand on each side, we show that price discrimination (i) increases participation on both sides, (ii) enhances total welfare, and (iii) may result in a strict Pareto improvement, with both seller types being better off than under uniform pricing. These results, which are in stark contrast to the traditional analysis of price discrimination, are driven by the existence of cross-group network effects. By improving the ability to monetize seller participation, price discrimination induces the platform to attract more buyers, which then increases seller participation. The Pareto improvement result means that even those sellers who pay a higher price under discrimination can be better off, because of the increased buyer participation. This paper was accepted by Joshua Gans, business strategy. Funding: A. de Cornière acknowledges funding from ANR [Grant ANR-17-EURE-0010] (Investissements d’Avenir program). Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2023.02788 .